The good dream - VanLiere, Donna, 1966- (St. Martin's Press, 2012)
Denounced by her 1950 Tennessee community as an old maid, 30-something Ivorie Walker hides her loneliness and grief over her mother's death behind good-humored independence before advocating on behalf of a feral boy who has been stealing vegetables from her garden.